Chapter 10: Bioanalytical Methods (Analytical Methods for Drug Development, 2025)
AuthorMr. N V Murali KrishnaAssociate Professor, Dept of Pharmaceutical Analysis, Nirmala College of Pharmacy, Ukkayapalli, Kadapa, Andhra Pradesh, IndiaAbstractBioanalytical methods quantify drugs and metabolites in biological matrices with high sensitivity and specificity. Bioavailability studies require analysis of plasma, urine, and tissue samples with extraction protocols tailored to drug properties and matrix complexities. Method selection considers sensitivity requirements, sample volumes, throughput needs, and available instrumentation. Pharmacokinetic analysis requires precise sample collection timing, stability controls, and accurate concentration measurements to generate time-profiles and calculate parameters like AUC, Cmax, and half-life. Validation follows FDA and EMA guidelines, establishing selectivity, sensitivity, accuracy, precision, and stability under various storage and handling conditions. Matrix effects in LC-MS/MS manifest as ion suppression or enhancement, requiring assessment through recovery studies and matrix factor determination. Sample preparation techniques including protein precipitation, liquid-liquid extraction, and solid-phase extraction remove interferents while maintaining recovery and reproducibility.Keywords: Bioanalytical Method Validation, LC-MS/MS, Pharmacokinetics, Plasma Drug Quantification, Biological Sample Extraction, Matrix EffectVIEW PDF